Introducción para el análisis de las Políticas Públicas - Röth Deubel, André Noel (Cuadernos de Administración, 2003)
In Colombia the investigation on public policies is still incipience in spite of a remarkable growth of the interest by the developed subject so much in the academic field as political-administrative. With the present article it is tried to introduce of simple wo)! to the reader in the subject of the analysis of the public policies. Through the comfortable key of reading of the call cycle of public policies, one briefly appears the main concepts used by this field ofstudy: definition, problems, agenda, formulation, decision, implementation and evaluation. One is an invitation to the development of works of investigation in this area of social sciences that is characterized as much by its connection with the theoretical reflection as with the analysis of political, social, economic and administrative the reality from a interdisciplinary perspective.